O cadastro ambiental rural como ferramenta de estudo do uso e apropriação da paisagem rural goiana - Souza, Cristiane Silva e (2016)
This research aimed to systematization of state and federal forest legislation, in particular that in State of Goiás, with regard to the informations that must be included in the Rural Environmental Registry (CAR) and presents the contributions of this tool to operationalize the Forest Code and, at the same time, its inconsistencies. The use and occupation of land in State of Goiás should be understood as a determining factor for intensifying landscape artificialization1. In State of Goiás the favorable physical aspects and public policy were determining factors for intensification of land use and increased deforestation. With the publication of law 12.651, on May 25th, 2012, which was designed to protect the native vegetation, the instrument of CAR, became mandatory for all rural properties. This instrument, CAR, is a strategic tool in helping environmental regularization of rural property and whose main objective is monitoring and control of deforestation. The state and federal Forest Codes committed environmental injustices to treat different the small and large landowners, grant amnesty to the owners that have established areas (environmental liabilities that occurred before July 22th, 2008), allow smaller legal reserve areas and permanent preservation to properties with up to four fiscal modules, and broad legalization opportunities in the Environmental Adjustment Program (PRA), in contrast to the defense of the balanced environment. The methodology involves applied research regarding the classification of its nature. Through the prism of how to approach the problem, it is a qualitative and quantitative research. As for the goals, it has an exploratory and explanatory research at the same time. With regard to technical procedures, research is classified as bibliographic and documental. In this research was done an exploratory historical approach and of cartographic base, resulting in a explanatory text, the achievement of interpretations, readings and correlations of images, tables, maps, and other products that will serve as a theoretical framework for future studies on the territorial environmental planning. It was observed that within two years, 2014-2016, were recorded in State of Goiás, 101,943 properties in the CAR, approximately 44% of rural properties in the state. Declarations of areas of permanent preservation, legal reserves and surplus vegetation to environmental servitude totaling 4,117,485 hectares, equivalent to 12.11% of the total area of the state, while 3.63% of its territory is protected in the form of conservation units, without considering the municipal protected areas. Approximately 21,469 of the registered properties recognized a deficit of native vegetation in legal reserve, in which 20.32% have chosen to settle with compensation, 20.07% with replanting and 12.56% with natural regeneration of the vegetation. The artificiality in State of Goiás countryside is evident in the declared registers, since joining the PRA was 43.16% of registered properties. Of the 18,086,334 hectares of declared properties, 3,140,972 hectares are legal reserves, equivalent to 17.37% of the area of the registered properties, so an approximate deficit of 2.63%. 2,438,985 hectares of legal reserve was recorded with remaining native vegetation, since the areas of permanent preservation of registered 976,513 hectares, 611,397 hectares have declared vegetation.